Unpacking the stranger: Examining the lives of Darfuris in Amman and Cairo - Habersky, Elena (AUC Knowledge Fountain, 2018)
This thesis examines the lives of two categories of individuals in particular socials: The Darfuri Refugee in Amman and the Deported Darfuri in Cairo. This thesis will first examine how, in the first country of exile, the Darfuri Refugees in Amman are able to gain trust of one another and make sense of their past and present lives of fragmentation by re-constructing parts of their shared history. By doing this, it becomes easier for the Darfuri Refugee in Amman to assemble together in tight-knit community structures which support one another in navigating Amman as perceived strangers to the resident community while they all await a next step on their journeys. This thesis will then examine how, by performing politically, namely, protesting outside of UNHCR, the Darfuri Refugee in Amman became the Deported and ultimately used transnational relationships and knowledge to cross the border from Sudan into Egypt to become the Deported Darfuri in Cairo. Once again, the Deported Darfuri in Cairo re-assembled their community structure to help them in navigating the social of Cairo as strangers who had undergone traumatic experiences. Throughout these assemblages and re-assemblages, the Darfuri Refugees find themselves in communities of support in order to live their lives in exile as the perceived strangers within their two socials. From their entire migratory experiences, which consists of fragmented journeys, this thesis argues how the migratory experiences involves reconciling the simultaneous need for visibility from international organizations and invisibility from the resident communities in order to safely live their lives in exile.